YIELD PERFORMANCE AND ADAPTATION OF PROMISING AMPHIBIOUS RED RICE LINES ON SIX GROWING ENVIRONMENTS IN LOMBOK, INDONESIA - Aryana, I.G.P. Muliarta; Wangiyana, W. (AGRIVITA, Journal of Agricultural Science, 2016)
The objectives of this study were to examine yield performance of promising amphibious red rice lines, and to evaluate their adaptability to six growing environments in Lombok, Indonesia. Ten promising amphibious red rice lines were tested together with their three parents and one national cultivar (Aek Sibundong), during the rainy extended to dry season 2014 (January-June 2014). The ten promising lines were obtained from two population sources, while the three parents were AKBC52, AKBC86, and a local cultivar, i.e. Kala Isi Tolo (KIT). The testing environments were lowland in Mambalan village (West Lombok), medium highland in Mantang village (Central Lombok), and highland in East Sembalun village (East Lombok), and each location consisted of two systems, i.e. flooded and dry (upland) systems. The experiment in each environment was designed according to Randomized Complete Block Design, with three replications and 14 genotypes as the treatments. Adaptation analysis was based on ANOVA using AMMI and Biplot. The results indicated that among the 14 genotypes, G10(F2BC4A52-42) showed the highest yield, with an average of 7.8 t ha-1 dry seeds. There was a significant Genotype x Environment interaction on the dry seed yield. Biplot analysis indicated that G2(F2BC4A52-44) and G8(F2BC4A52-37)